A study of relative value of percutaneous fine needle aspiration cytology and bronchoscopy in pulmonary lesions - Srivastava, Anand; Kumar, Awdhesh; Joshi, Ambarish; Kumar Verma, Ajay; Chaudhri, Sudhir; Kant, Surya (International Journal of Medical Research and Review, 2016)
Percutaneous fine needle aspiration cytology (FNAC) is a useful additional method for establishing a diagnosis of intrathoracic lesions without a thoracotomy. Aims and Objective: To study the comparative role of FNAC. 1) In establishing the diagnosis of intrathoracic solid lesions. 2) Its role in improving the diagnostic yield. Material and Methods: All the patients, irrespective of their age and sex, who presented with space occupying lesions in thorax, large nodular shadows and consolidation on clinico-radiological ground, were included in the study and subjected to FNAC and other procedures like fiberoptic bronchoscopy (FOB) etc. Results: 44 patients were enrolled in the study. 56.8% cases were diagnosed as primary carcinoma lung and 6.8% as benign lesions, while 36.4% cases could not be diagnosed by any means. 28 cases were diagnosed either by means of FNAC and / or by other methods of investigation like FOB and sputum cytology. Overall diagnostic yield of FNAC was 54.5%, with positivity more in central lesions (66.7%) than in peripheral lesions (46.2%). Diagnostic yield of FNAC for malignancy was 84%. Overall diagnostic yield by bronchoscopy was 17/44(38.6%). FNAC was also effective to pick up diagnosis in 13(29.5%) but failed in 4 cases which were diagnosed by bronchoscopy. Overall 6.8% patients developed minor complications. Conclusion: Considering its simplicity, safety, rapidity, cost effective and high diagnostic accuracy FNAC can be and should be performed as an initial diagnostic measure, preceding bronchoscopy, mediastinoscopy and thoracotomy whenever exfoliative sputum cytology has failed to establish the diagnosis of the entire peripheral and selected intrathoracic lesion.